2020
DOI: 10.1186/s12959-020-00234-x
|View full text |Cite
|
Sign up to set email alerts
|

GST null polymorphisms may affect the risk of coronary artery disease: evidence from a meta-analysis

Abstract: Background: Whether glutathione S-transferase (GST) null polymorphisms, namely GSTM1 null, GSTP1 null and GSTT1 null polymorphisms, influence the risk of coronary artery disease (CAD) or not remains unclear. Thus, the authors performed a meta-analysis to more robustly estimate associations between GST null polymorphisms and the risk of CAD by integrating the results of previous publications. Methods: Medline, Embase, Wanfang, VIP and CNKI were searched comprehensively for eligible studies, and 45 genetic assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…We focused on genetic variants of candidate genes which have been associated with the pathogenesis of coronary atherosclerosis. They, play key roles in the inactivation of pro‐oxidants and pro‐inflammatory mediators, lipid and xenobiotic metabolism, detoxification of reactive oxygen species, and regulation of cellular proliferation during the development of atherosclerosis (Almontashiri, 2017; Bhattacharyya et al, 2008; Su et al, 2020). These variants occur in Paraoxonase 1 ( PON1 , OMIM 168820), Glutathione S‐transferase M1 ( GSTM1 , OMIM 138350), Glutathione S‐transferase T1 ( GSTT1 , OMIM 600436), and a 58‐kb interval on chromosome 9p21.3 (OMIM 611139).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on genetic variants of candidate genes which have been associated with the pathogenesis of coronary atherosclerosis. They, play key roles in the inactivation of pro‐oxidants and pro‐inflammatory mediators, lipid and xenobiotic metabolism, detoxification of reactive oxygen species, and regulation of cellular proliferation during the development of atherosclerosis (Almontashiri, 2017; Bhattacharyya et al, 2008; Su et al, 2020). These variants occur in Paraoxonase 1 ( PON1 , OMIM 168820), Glutathione S‐transferase M1 ( GSTM1 , OMIM 138350), Glutathione S‐transferase T1 ( GSTT1 , OMIM 600436), and a 58‐kb interval on chromosome 9p21.3 (OMIM 611139).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have indicated that the GSTM1 and GSTT1 null variants are associated with an increased risk of CAD, especially when several other factors, such as diabetes mellitus, hypertension, and cigarette smoking, are present (Grubisa et al, 2018; Kariž et al, 2012; Kim et al, 2008; Mir et al, 2016; Tamer et al, 2004). Likewise, the GSTM1 null genotype has been associated with the risk of CAD from a meta‐analysis in Caucasians, Asians, and mixed populations, whereas the GSTT1 null polymorphism was significantly associated with the risk of CAD in the overall population, Caucasians and East Asians (Su et al, 2020). In addition, the combined GSTM1/T1 null genotypes have been associated with the susceptibility to the development of CAD (Grubisa et al, 2018; Kim et al, 2008; Zhang & Zhang, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, one previous meta-analysis, conducted by Su et al [24], included 4,595 cases and 4,390 controls from 11 studies. They proved that GSTP1 null polymorphism was associated with the risk of CHD in the overall population (OR, 1.23; 95% CI, 1.02 to 1.48).…”
Section: Plos Onementioning
confidence: 99%
“…A number of case-control studies [4,7,8,[12][13][14][15][16][17][18][19][20][21][22][23] have investigated the relationship between GSTP1 Ile105Val polymorphism with the risk of CHD, with equivocal conclusions. Recently, one meta-analysis [24] revealed that a significant association exists between GSTP1 null genotype and CHD, and the other one [25] suggested that GSTP1 null genotype could impact individual susceptibility to atherosclerotic cardiovascular diseases. However, numerous relevant publications [4, 19,22,23] did not appear in their meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Além da frequência dos genótipos nulos, a análise da presença/ausência de GSTM1 e de GSTT1 também foi empregada em investigações sobre a susceptibilidade de diferentes doenças como asma (Li et al, 2013), diabetes mellitus (Zhang et al, 2013a;Nath et al, 2019), doenças arteriais e coronarianas (Zhou et al, 2014;Grubisa et al, 2018;Su et al, 2020), hipertensão (Ge et al, 2015) e diferentes tipos tumorais (Sampaio et al, 2009). Dentre os resultados, foi demonstrada que os genótipos nulos de GSTM1 e de GSTT1 foram associados, de forma individual, ou em combinação entre si, com o aumento do risco de diabetes mellitus (Zhang et al, 2013;Nath et al, 2019) e de distúrbios arteriais (Grubisa et al, 2018).…”
Section: Variabilidade Do Número De Cópias De Gstm1 E De Gstt1unclassified